Estudo da alumina anódica porosa como sensor para diferentes gases - Guerreiro, Haroldo de Almeida (2013)
In this project we studied the porous anodic alumina as a possible application in gas sensors with high sensitivity. Initially we seek a configuration of anodic porous alumina (PA) and the type of gas or vapor in which both matched with great sensitivity by observing the photoluminescence of this material. Furthermore we sought to understand the mechanism of detecting the substance to a broader reach and optimizing the use of alumina sensor. A manufacturing already well tested with oxalic acid, only changing the anodization time for the same voltage or current density, was adopted for a small variation of samples with good ordering. Samples were also produced with and without pore opening. The optical properties of the porous film thus obtained were investigated by photoluminescence (PL) emitted perpendicularly to these pores, while the film was subjected to a controlled atmosphere of vapor of ethanol or methanol. The control parameters of temperature and vapor concentration was possible by the construction and use of a thermostated cell adapted to a spectrofluorimeter. The spectrum of each sample was monitored with time since deposition of alcohols in the cell was made with micro-syringe into the liquid phase and then evaporate. This perpendicular direction of luminescence emission of alumina allowed the oscillation of the already known PL presents peaks with much more defined and so much more resolution for changes in wavelength. Furthermore, it expressed the presence of the TE and TM modes separately in luminescence for some samples made at a higher concentration of oxalic acid in the electrolyte. The sensitivity to ethanol vapor for this PL technique allows detection of ethanol concentrations much smaller than the other until now achieved by using porous silicon. Based on studies about the source of the luminescence of the material and the construction of the interference pattern produced by the film type Fabry-Perot, a hypothesis was constructed for the modification of luminescence by ethanol vapor. Adsorption of molecules of ethanol/methanol by its hydroxide OH-, in the color centers F+ along the surfaces of the pores, modifies the average longitudinal position of the sources of luminescence in a critical geometry (near total internal reflection), which changes rapidly the reflectivity of the interface pores/air, altering the entire Fabry-Perot system for this adopted configuration, i.e., PL perpendicular to the pores. The simple change of the luminescence emission from frontal to lateral direction of the film provided an peak oscillation with lasers devices width, without the need to optically confine this film, as in the case of porous silicon sensors. This configuration may have contributed to or be reason for the great sensitivity (relative to the optical porous sensors for ethanol as the porous silicon) as it uses the part of the luminescence that interacts with more pores exposed to ethanol vapor. The reversible behavior and with better response just at room temperature, qualifies the PA system for construction of curves calibration, as well for various types of use in sensor which interfere very little in vapor concentration. The temporal behavior of the spectrum of a sample, under ethanol vapor, may be due to a rapid change in reflectivity of the interface pores/air for this selected PL "grazing", at an angle close to the internal total internal reflection. The change in reflectivity for this type of Fabry- Perot system and confined causes changes in both the shape of the spectrum oscillation, similar to the change in the coefficient of finesse, as in the displacement of the peak position in wavelengths.